Experimental study of impact on carbon-fiber-epoxy composite wing leading edge structure - Omar, Nurihan; Aminanda, Yulfian; Syed Mohamed Ali, Jaffar (Trans Tech Publications Ltd., Switzerland, 2014)
This paper works on the curvature composite structure for wing leading edge application using fabric carbon/epoxy material subjected to impact loading. At first stage, rigid spherical projectile and elliptical panel with were used. The impact testing has been carried out by varying the radius of curvature, the thickness of the panel and different stacking sequence. The experimental results show the trend of specific energy absorption capability of structure in function of the radius, thickness of panel and carbon fiber directions.